Simple Sensitive Spectrophotometric Determination of Vanadium in Biological and Environmental Samples - B. Krishna Priya; P. Subrahmanyam; J. Dilip Kumar; P. Chiranjeevi (E-Journal of Chemistry)
Novel, rapid, highly sensitive and selective spectrophotometric method for the determination of traces of vanadium (V) in environmental and biological samples, pharmaceutical and steel samples was studied. The method is based on oxidation of 2,4- dinitro phenyl hydrazine(2,4-DNPH) by vanadium (V) followed by coupling reaction with N-(1-naphthalene-1-yl)ethane-1,2-diamine-dihydrochloride (NEDA) in acidic medium to give red colored derivative or on oxidation of 4-Amino Pyridine by vanadium (V) followed by coupling reaction with NEDA in basic medium to give pink colored derivative. The red colored derivative having an λmax 495 nm which is stable for 8 days and the pink colored derivative with 525 nm is stable for more than 7 days at 350C. Beer's law is obeyed for vanadium (V) in the concentration range of 0.02 - 3.5 μg mL–1 (red derivative) and 0.03 – 4.5 μg mL–1 (pink derivative) at the wave length of maximum absorption. The optimum reaction conditions and other analytical parameters were investigated to enhance the sensitivity of the present method. The detailed study of various interferences made the method more selective. The proposed method was successfully applied to the analysis of vanadium in natural water samples, plant material, soil samples, synthetic mixtures, pharmaceutical samples and biological samples. The results obtained were agreed with the reported methods at the 95 % confidence level. The performance of proposed method was evaluated in terms of Student's t-test and Variance ratio f-test which indicates the significance of proposed method over reported method.